2020
DOI: 10.1007/s00705-020-04773-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and full-genome sequencing of canine kobuvirus in canine fecal samples collected from Anhui Province, eastern China

Abstract: Canine kobuvirus (CaKoV), a newly described virus, is the causative agent of gastroenteritis in dogs. In this study, 57 fecal samples from dogs with diarrhea in Anhui Province, eastern China, were collected. Among these, five samples were identified to be infected with CaKoV, by polymerase chain reaction targeting the CaKoV 3D gene. The five CaKoV strains were subjected to phylogenetic analysis. The sequences of VP1 from the five CaKoV strains were 93.6%-96.1% identical to each other and 91.75%-97.95% identica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The phylogenetic analysis based on our complete VP1 nt sequences (with the murine rodent host species shown in italics) indicates that our VP1 sequences clustered closely with those from China but were separated from MuKV VP1 sequences from Hungary and Vietnam (). This demonstrates that the MuKV sequences from China may share a similar evolutionary background and circulate among the various murine rodent populations in China [48]. This provides evidence of geographic clustering of the analysed VP1 sequences, though geographic clustering was not observed regarding the 3D region.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The phylogenetic analysis based on our complete VP1 nt sequences (with the murine rodent host species shown in italics) indicates that our VP1 sequences clustered closely with those from China but were separated from MuKV VP1 sequences from Hungary and Vietnam (). This demonstrates that the MuKV sequences from China may share a similar evolutionary background and circulate among the various murine rodent populations in China [48]. This provides evidence of geographic clustering of the analysed VP1 sequences, though geographic clustering was not observed regarding the 3D region.…”
Section: Discussionmentioning
confidence: 81%
“…2 ). This demonstrates that the MuKV sequences from China may share a similar evolutionary background and circulate among the various murine rodent populations in China [ 48 ]. This provides evidence of geographic clustering of the analysed VP1 sequences, though geographic clustering was not observed regarding the 3D region.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the analysis results suggest that cross-species transmission of Kobuviruses exists. As companion animals, canines and felines have very close contact with humans, and canine and feline Kobuvirus can be detected in feces [ 3 , 72 ], which makes it possible for the virus to spread to canines and felines through fecal-oral transmission. To further understand the relationship between different species of Kobuvirus, after analyzing the amino acid sequence and structure of the VP1 protein, we found that there are two motifs with >95% homology in mammalian Kobuviruses, except for rabbit and bat Kobuviruses ( Figure S1 ), and both motifs are exposed on the exterior of the VP1 protein ( Figure 4 and Figure S2 ), suggesting that these two motifs may be key points for Kobuvirus to infect different mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that there is a recombination event in PKV [ 26 ]; therefore, recombination might play an important role in the evolution of PKV. In recent years, Kobuviruses have been found in other animals, including bats, canines, felines, and goats, they are quite different from previous Kobuviruses [ 3 , 11 , 27 ]. An epidemiological survey of Kobuviruses in Vietnam found frequent cross-species transmission of Kobuviruses both within and among mammalian species [ 11 ].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation